Analisis kinerja pemungutan retribusi pemanfaatan tanah milik pemerintah Kota Malang - Cindy Getah Trisna June; Muhammad Syafiq Muhammad Syafiq; Ary Yunita Anggraeni; Fitriana Santi; Dyah Paramitha (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2026)
The utilization of land owned by the Malang City Government through a leasing scheme represents an effort to optimize regional assets that not only provides economic benefits to the community but also serves as an important source of Local Own-Source Revenue (PAD). The levy imposed on the utilization of these assets constitutes compensation for the use of government-owned property by individuals or third parties. Therefore, the effectiveness of the levy collection system plays a crucial role in optimizing regional revenue. This study aims to evaluate the levy collection system for the utilization of Malang City Government land and to identify the factors affecting its effectiveness. A descriptive qualitative approach was employed using observation, interviews, documentation, and surveys involving land tenants across five districts in Malang City. The findings indicate that the effectiveness of levy collection is constrained by several issues, including the predominance of manual payment procedures, reliance on physical payment receipts that are prone to loss, complex leaseholder transfer administration, and the lack of integration between the payment information system and the regional asset database. Respondents also expressed the need for digital payment systems to improve convenience, transparency, and service accountability. The findings are expected to provide a basis for developing digital transformation strategies in regional levy management to enhance public service quality and optimize Local Own-Source Revenue in a sustainable manner.